Sepsis severity in chronic intestinal failure patients presenting with catheter related blood stream infection - Ashley Bond; Maja Kopczynska; Antje Teubner; Arun Abraham; Jaclyn Salt; Maria Barrett; Simon Lal (Intestinal Failure)
Introduction: The occurrence of catheter related blood stream infection (CRBSI) is a leading cause of morbidity and mortality for patients receiving home parenteral support (HPS) via a central venous catheter (CVC), as part of their chronic intestinal failure (CIF) care. Methods: This was a retrospective cohort study of CRBSI events in patients receiving HPS for underlying CIF, cared for at a national IF Reference Centre between 2012 and 2022. Results: Overall, there were 153 CRBSI episodes recorded in 102 patients, over 418,252 catheter days, corresponding to CRBSI rate of 0.37 per 1000 catheter days. Among all episodes of CRBSI, 79 (51.6 %) had SIRS ≥ 2, 55 (35.9 %) had SOFA ≥ 2, 35 (22.9 %) had Red Flag sepsis and 28 (18.3 %) fulfilled NICE high-risk criteria. Of note, substantial proportion of episodes (35.3 %) did not fulfil any of the criteria. The median score for SIRS criteria was 2 (IQR 0–3) and for SOFA was 1 (IQR 0–2). The median white cell count was 8.3 × 109/L (IQR 6.2–14.0 ×109/L), median C-reactive protein was 44.0 mg/L (IQR 14.0–90.0 mg/L). There were no CRBSI-related deaths recorded among the study population. Eight (5.2 %) CRBSI episodes led to multi-organ dysfunction and in 10 (6.5 %) episodes patients required ICU admission. Conclusions: We have demonstrated that the majority of HPS-dependent patients who present with CRBSI do so in a subtle manner. Awareness of this is vital, particularly for healthcare professionals who do not routinely care for patients with CIF.